EKONOMICZNA ANALIZA ODPOWIEDZIALNOŚCI AKWILIAŃSKIEJ - PARADOKS CZY NOWA MOŻLIWOŚĆ ANALIZY ANTYCZNEJ REGULACJI PRAWNEJ - Święcicka, Paulina (Zeszyty Prawnicze, 2017)
Economic Analysis of Responsibility ex lege Aquilia - an Analytic Paradox or a New Possibility of Analysis of the Ancient Law Summary During the last 200 years, economists have made important contributions to the analysis of many areas of law. Nevertheless, it is only during the last 25 years when the economists and legal scholars – have turned their attention in a systematic way to the analysis of torts, contracts, and criminal law. In spite of the youth of the sub-discipline that examines these branches, it has quickly become a discipline of great significance in the U. S. and, to a lesser extentin, Europe. We can also say, that the economic analysis of the tort liability is one of the most important achievements of law and economics. The main economic insight is that exposure to tort liability may induce potential victims and injurers to take actions before an accident occurs, which will minimize the social costs of accidents (where these social costs include the precautionary costs of victims and injurers, the accident losses suffered by both parties and the administrative costs of determining liability). In early times a person was held liable for wrongdoing if he acted without right (iniuria), and only if the death or the injury was the result of a direct contact between the body of the wrongdoer and the thing. After this period, in classical times, after an extensive interpretation of the text of the above mentioned lex, the wrongdoer had also be willful, negligent and reasonably foreseeable, i.e. his acting had to include dolus or culpa (neglegentia) . It is also obvious that the modern civil law constantly revolves around the terminology and constructions formed in the Roman law or on the grounds of the Roman law. One of aims of this paper is to show the similarities and the influences of Roman law on the modern legal systems in the sphere of civil liability founded on a principle o f fault- culpa. Another one is to elucidate possible factors which may lay under the development of this ancient concepts and also to attempt to establish a framework for examination of Roman legal rules through the intellectual apparatus provided by the modern Law & Economics.